If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(8x + 6) = 3x + -40 Reorder the terms: 9x + -1(6 + 8x) = 3x + -40 9x + (6 * -1 + 8x * -1) = 3x + -40 9x + (-6 + -8x) = 3x + -40 Reorder the terms: -6 + 9x + -8x = 3x + -40 Combine like terms: 9x + -8x = 1x -6 + 1x = 3x + -40 Reorder the terms: -6 + 1x = -40 + 3x Solving -6 + 1x = -40 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 1x + -3x = -40 + 3x + -3x Combine like terms: 1x + -3x = -2x -6 + -2x = -40 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -2x = -40 + 0 -6 + -2x = -40 Add '6' to each side of the equation. -6 + 6 + -2x = -40 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = -40 + 6 -2x = -40 + 6 Combine like terms: -40 + 6 = -34 -2x = -34 Divide each side by '-2'. x = 17 Simplifying x = 17
| 17-3k=8k+7(6+2k) | | 20x+16=25 | | -115b+80=-489 | | 5m+(m+1)=23 | | 8n-3(n-1)=-5+33 | | 3(h-2)=18 | | g^3(3g^3-13)= | | -115b+80=-89 | | -115b+80=-49 | | -x-8=4 | | 4(3x-2)-5x=6-(2x-1) | | 3(x-2)=-36-7x | | .5b+4=2+3d-.5 | | 2x+10=x-6 | | -97=6(3n-2)-n | | 2p-2(6-2p)=2(p-5)-2 | | -3n-16=7(n+2) | | -3(4x-15)-8(3x-5)= | | 5d-2-d= | | -4y-8y=-15 | | 9x=9x+18 | | 9y=-1 | | 35+8r=7(2r-1) | | 5x-6=5x-x | | 6-x=-24 | | 3w-5-19w^2+17= | | 8(v+1)-4v=2(2v+2)-8 | | -5(1-5x)=-8x-5 | | 3+25+15x=58 | | 8y+4-6y=7+y-6 | | 2.4p-5=9.4 | | -6v-5(v+5)=-6v-5 |